P096 Characterization of suppressive immune cell subsets in mouse models of colitis-associated colorectal cancer. (30th January 2023) - Frigerio, S; Saris, J; Franco Fernandez, R; Koelink, P; van Roest, M; Wildenberg, M; D'Haens, G; Grootjans, J
Abstract: Background: Chronic colonic inflammation in inflammatory bowel disease (IBD) patients increases the risk of colitis-associated cancer (CAC). Cancer development in CAC is different from that observed in sporadic colorectal cancer (CRC). Most studies have focused on the role of pro-inflammatory immune cell subsets in CAC, yet it is becoming increasingly clear that immunosuppression may also drive cancer progression. We hypothesize that emergence of immunosuppressive cell subsets as a result of chronic intestinal inflammation, dampens anti-tumor immune responses and accelerates the development of CAC. Methods: To simulate cancer formation in the background of chronic inflammation, mice were treated with azoxymethane (AOM) followed by three cycles of dextran sodium sulphate (DSS). Apc Min/+ mice treated with AOM were used to model sporadic CRC. After 10 weeks, immune cells from the proximal and distal colonic lamina propria, mesenteric lymph nodes (MLNs) and tumors were obtained for microscopy analyses and processed to obtain single cell suspensions for flow cytometry. Immune cell populations were studied by conventional flow cytometry and immunofluorescence. Results: We observed a significant increase in absolute numbers of PD1 + CTLA4 + TIM3 + 'exhausted' CD4 + T cells in the lamina propria from proximal colons in CAC mice as compared to sporadic CRC mice. Interestingly, these numbers showed a positive correlation with the inflammation score in AOM/DSS, demonstrating that chronic inflammation is associated with the emergence of 'exhausted' T cells. In addition, we observed a trend to higher numbers of M2-like (MHCII - CD206 + ) suppressive macrophages and CD4 + FoxP3 + regulatory T cells (Tregs) in tumors from CAC mice compared to sporadic CRC. When analysing T cell immune responses in the MLNs, we found a significant decrease in the ratio IFNγ/IL10-producing CD8 + T cells in CAC mice as compared to CRC mice, suggesting a shift towards an anti-inflammatory T cell response in CAC. Conclusion: In summary, suppressive immune cell subsets were increased in colonic mucosa and tumors from CAC mice as a result of chronic inflammation, which may be associated with the development of dysplasia. Further functional studies are necessary to prove the role of suppressive immune subsets in IBD-associated dysplasia- and carcinoma progression.